Erudizione municipale e fonti documentarie Archivi e ricerca storica nell'Ottocento italiano (1840-1880) - Andrea Giorgi (Reti Medievali E-Book, 2019)
In the middle decades of the 19th century (also known as the "History century"), the archives opened to historical research in Italy as well, starting to raise new awareness on the importance of documentary sources from the Medieval and Modern Ages. The network of State Archives was organised gradually; however, before and after the Unification of Italy, cities, "municipal" scholars and their networks of relationships, as well as city archives and institutions, remained a dominant element. Using classification essays and a series of researches on individual citizen contexts from the whole Italian Peninsula, this volume explores the variety and richness of this transformation, in the country's centre and in the suburbs.